A Phase I/II, Prospective Multi-Center Study of the Safety and Preliminary Efficacy of Intravenous Allogeneic Mesenchymal Bone Marrow Cells in Chronic Ischemic Stroke. (1st September 2019) - Levy, Michael L; Crawford, John; Dib, Nabil; Verkh, Lev; Tankovich, Nikolai; Cramer, Steven C
Abstract: INTRODUCTION: Stroke is a leading cause of disability, affecting patients for years. We examined safety and preliminary efficacy for a cellular therapy targeting patients with chronic disabling stroke, a population for whom limited treatment options currently exist. METHODS: Entry criteria included ischemic stroke > 6 mo prior, substantial disability (subject confined to wheelchair, had home-nursing care, or needed assistance with activities of daily living), and NIH Stroke Scale (NIHSS) score = 6 to 20. Enrollees received a single intravenous dose of allogeneic mesenchymal bone marrow cells. Phase 1 used a dose escalation design (3 tiers, n = 5 each). Phase 2 (n = 21) was an expanded safety cohort. The primary endpoint was safety over 1-yr. Secondary endpoints examined behavior, with a pre-specified focus at 6-mo. RESULTS: In phase 1, each dose (0.5, 1.0, and 1.5 million cells/kg body weight) was found safe, so phase 2 subjects received 1.5 million cells/kg. At baseline, subjects (n = 36) averaged 4.2 ± 4.6 yr poststroke, age 61.1 ± 10.8 yr, NIHSS score 8.7 ± 3.0, and Barthel Index 65 ± 29. Two were lost to follow-up, one was withdrawn, and two died (unrelated to study treatment). There were 15 serious adverse events, none possibly or probably related to study treatment. Two adverse events were possibly related to study treatment, a UTI and IV site irritation. Treatment was safe based on serial exams, EKGs, laboratory tests, and pan-computed tomography scans. Change from baseline to 6-mo post-transfusion was significant for all 4 secondary endpoints: Barthel Index (6.8 ± 11.4 points, P = .002), NIHSS (−1.25 ± 1.7 points, P < .001), MiniMental Status Exam (1.8 ± 2.8 points, P < .001), and Geriatric Depression Scale (−1.6 ± 3.8 points, P = .015). At baseline 11.4% (4/35 subjects) had Barthel Index = 95 to 100 (favorable outcome); at 6-mo, 27.3% (9/33); by 12-mo, 35.5% (11/31). CONCLUSION: Transfusion of mesenchymal bone marrow cells in patients with disabling chronic stroke was safe and significantly improved several behavioral measures. The initial results were potentially equivalent to or exceeded those of prior studies utilizing stereotactic implantation. These data support proceeding to a randomized, placebo-controlled study.